(untitled) (Education in the 21st Century, 2023)
Brief introduction. Education is a vehicle of change that is operationalized and further fueled through several interconnected gears, such as globalization, technological advancements, geopolitical, and socio-cultural rapid developments. These transformative metaprocesses have created the necessity of radical and systemic transformations in the current higher education system in Armenia. Consequently, the higher education system in Armenia faces numerous challenges and problems that are mainly conditioned by the requirements stipulated by the development of knowledge-based economy, educational innovations, and innovative technologies. On the other hand, the lack of national strategy on higher education at state level and limited targeted state funding have exacerbated the situation. Consequently, the Armenian higher education system is lagging from international developments, and there is a mismatch between the current delivery of higher education and market needs in Armenia. If this lagging continues in the long run, it will eventually create the “intellectual bankruptcy” of higher education system in Armenia. Thus, the Government of the Republic of Armenia (RA) should develop and endorse a competitive higher education strategy and innovative university strategic management models. These two constructs should be comprehensively developed for the coming decade in close cooperation with all higher education stakeholders, including the RA universities. It is also necessary to ensure the development of efficient university strategic management models, the deployment of which will enable universities to develop their strategic management processes and will align human, financial and other resources to the implementation of national strategy of higher education, state priorities, and long-term development of higher education in Armenia.